Clinical impact of a sub-epidermal moisture scanner: what is the real-world use?. (2nd March 2021) - Musa, Louisa; Ore, Nicky; Raine, Gillian; Smith, Glenn
Abstract : Objective: The presence of sub-epidermal moisture (SEM) over a bony prominence is indicative of incipient pressure ulcer (pressure injury/decubitus/bedsore) (PU). Early identification of patients at increased risk of PU can prompt interventions that reduce the incidence and severity of hospital (or community)-acquired PUs (HAPUs). This study evaluated the clinical utility of a SEM Scanner device in HAPU management. Method: The study used a pragmatic 'real-world' approach. HAPU data before and during SEM Scanner use were obtained through routine audit. Patients had regular visual and daily SEM Scanner skin assessments over the sacrum and heels. Nursing care otherwise followed standard of care according to the established protocols of individual participating sites. HAPU incidence rates were determined and feedback gathered from health professionals on how the device influenced HAPU-related clinical decision-making. Results: There were 15 participating sites: 13 acute care, one palliative care and one community care setting. The sample size was 1478 patients. All sites reported a substantial reduction in mean HAPU incidence: 87.2% in acute care settings; 46.7% in the palliative care setting and 26.7% in the community care setting. A 100% incidence reduction was reported in 10 (66.7%) sites. In the palliative care setting, SEM Scanner results changed HAPU-related clinical decision-making for 40% of patients scanned. The community care site demonstrated a 82% change in clinical decision-making. Conclusion: In this study, SEM analysis fitted seamlessly into routine skin assessment and enabled early identification of increased risk of tissue damage, with clinically important reductions in the incidence of HAPU across all participating sites.